2018
DOI: 10.3389/fchem.2018.00224
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Metal-Based Imaging Probe for Targeted Dual-Modality SPECT/MR Imaging of Angiogenesis

Abstract: Superparamagnetic iron oxide nanoparticles with well-integrated multimodality imaging properties have generated increasing research interest in the past decade, especially when it comes to the targeted imaging of tumors. Bevacizumab (BCZM) on the other hand is a well-known and widely applied monoclonal antibody recognizing VEGF-A, which is overexpressed in angiogenesis. The aim of this proof-of-concept study was to develop a dual-modality nanoplatform for in vivo targeted single photon computed emission tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…IONPs have been functionalized with epithelial growth factor (EGFR) antibodies for the diagnosis of breast cancer [ 274 ], pancreatic/stomach cancer [ 275 ] and brain cancer [ 276 ]. Because there is an established relationship between mutations involving overexpression or overactivity of EGFR and various types of cancer, this receptor is currently one of the most important targets in cancer research [ 277 279 ].…”
Section: Applications Of Ionps In Mrimentioning
confidence: 99%
“…IONPs have been functionalized with epithelial growth factor (EGFR) antibodies for the diagnosis of breast cancer [ 274 ], pancreatic/stomach cancer [ 275 ] and brain cancer [ 276 ]. Because there is an established relationship between mutations involving overexpression or overactivity of EGFR and various types of cancer, this receptor is currently one of the most important targets in cancer research [ 277 279 ].…”
Section: Applications Of Ionps In Mrimentioning
confidence: 99%
“…This is presumably due to the DMSA molecules attached to the iron oxide's surface through the COOgroup [40]. According to the previous studies [33], the interaction between the carboxylate head and the metal atom was classified as monodentate, chelating bidentate and bridging bidentate structures, and the separation ( ν) between the wave numbers of the [ν s (COO -)] and [ν as (COO -)] infrared bands can be used to determine the type of interaction between the carboxylate groups of the DA and the iron atom. Here, the largest ν values (200-320 cm -1 ) correspond to the monodentate structure, the smallest ν values (<110 cm -1 ) the chelate bidentate structure and the medium range ν values (140-190 cm -1 ) the bridging bidentate structure.…”
Section: Synthesis and Physicochemical Properties Of Ionpsmentioning
confidence: 84%
“…In vitro and in vivo studies have showed that cell viability and proliferation are not influenced by the DMSA coating of Fe 3 O 4 and Fe 2 O 3 NPs [32]. DMSA-coated IONPs therefore have the potential to be used as magnetic carriers to deliver high concentrations of radioisotopes to certain areas, for example, as single-photon emission computerized tomography (SPECT)/dual-modal MRI contrast agents [33].…”
mentioning
confidence: 99%
“…The pronounced lung uptake may be attributed to various factors, such as NP size and DMSA coating. 18 20 Most importantly, almost 2.5% ID/g of Ag 3 Au 1 Trp 1:2 NPs accumulated to the tumor sites at 30 min post-administration ( Figure 2D ). Generally, the ideal NP has to stay enough time to bloodstream in order to augment the possibility to reach the tissue of interest, after escaping the RES which is one of the major biological barriers that reduce NP accumulation to the target tissue.…”
Section: Discussionmentioning
confidence: 99%